A Novel p.G141R Mutation in ILDR1 Leads to Recessive Nonsyndromic Deafness DFNB42 in Two Chinese Han Families - Xueling Wang; Longhao Wang; Hu Peng; Tao Yang; Hao Wu (Neural Plasticity)
Genetic hearing impairment is highly heterogeneous. In this study, targeted next-generation sequencing (NGS) in two Chinese Han families identified a novel p.G141R homozygous mutation in ILDR1 as the genetic cause of the deafness. Consistent with the recessive inheritance, cosegregation of the p.G141R variant with the hearing loss was confirmed in members of both families by PCR amplification and Sanger sequencing. SNP genotyping analysis suggested that those two families were not closely related. Our study showed that targeted NGS is an effective tool for diagnosis of genetic deafness and that p.G141R in ILDR1 may be a relatively frequent mutation for DFNB42 in Chinese Hans.